The analysis of activities and social campaigns aimed at reducing children’s risk of traffic incidents - Goniewicz, Krzysztof; Goniewicz, Mariusz; Pawłowski, Witold; Czerski, Robert (Journal of Education, Health and Sport, 2017)
Road traffic accidents and falls are the cause of over 80% of serious injuries in children. However, injuries resulting in road accidents are the leading cause of children’s death, more common than cancer and birth defects. The paper presents ways to reduce the risk of children in traffic. Various technical improvements were pointed out that could improve the safety of children. It highlighted the important role of parents and children tutors in education on road safety. It was found that injury prevention should be a systematic and organized action. This should include both the elimination of threats and actions to reduce the risk and improve the in-hospital and pre-hospital care.